Study on Numerical Simulation of Surrounding Rock Structure Safety of Urban Underwater Shield Tunnel: A Case in Chongqing - Yang, Zeng-Qiang; You, Xiao-Ming; Jin, Hui-Wu (Shock and Vibration, 2024)
Based on the engineering background of shield construction of a subway section in Chongqing, which needs to pass through a park and there is a lake inside this park, this paper adopts theoretical analysis methods and numerical simulation calculation methods to explore the distribution law of the seepage field and the characteristics of water pressure in lining segments during shield tunneling. The results show that, during the whole excavation of a double-track tunnel with EPB shield, the maximum vertical effective stress is about 4.24 MPa, which is located at the arch foot of the tunnel. The maximum effective stress in the horizontal direction is about 3.61 MPa, which is located on both side walls of the tunnel in the horizontal direction; after the left and right tunnels are excavated in sequence, a “double precipitation funnel-shaped” pore pressure distribution is formed around the tunnel; during the construction of the shield tunnel, the vertical displacement and horizontal displacement of the surrounding rock show an increasing trend and gradually tend to be stable values of 24.09 mm and 25.28 mm; the segment vault has settlement, the maximum settlement is 21.8 mm, the arch bottom has uplift, and the maximum uplift is 24.4 mm. The maximum horizontal displacement of the segment appears on both sides of the arch waist, and the maximum horizontal displacement decreases with the increase of excavation steps; the positive bending moment of the lining segment is mainly distributed on both sides of the arch crown, and the negative bending moment is mainly distributed on both sides of the arch bottom. The axial force of the lining segment is compressive stress, and the maximum axial force is mainly distributed on both sides of the arch waist. The maximum normal shear stress occurs on both sides of the segment arch bottom. The study conclusions provide theoretical foundation and a new guidance for long-term safety evaluation of underwater tunnel structures.